INFRASTRUCTURE FACILITY NEEDS ANALYSIS CITY PARK IN THE NEW NORMAL ERA : (CASE STUDY: TAMAN ADIPURA MUARA ENIM) - Mita Hargianti; Nasution Nasution; Husnul Hidayat (LPPM Universitas Negeri Jakarta, 2023)
City parks are again crowded with people after COVID-19 to play, exercise and recreation, and Adipura Muara Enim Park is no exception. The Covid-19 pandemic is not certain to end. For this reason, the facilities available in city parks in the new normal era need to be conditioned so that they can provide optimal services and can support the government's efforts in handling COVID-19. The aim of the research is to analyze the need for infrastructure facilities and get the